Pancreatic neuroendocrine tumors: Nosography, management and treatment. (April 2016) - Orditura, Michele; Petrillo, Angelica; Ventriglia, Jole; Diana, Anna; Laterza, Maria Maddalena; Fabozzi, Alessio; Savastano, Beatrice; Franzese, Elisena; Conzo, Giovanni; Santini, Luigi; Ciardiello, Fortunato; De Vita, Ferdinando
Abstract: Pancreatic neuroendocrine tumors (pNETs) represent about 7% of all NETs, 8.7% of gastroenteropancreatic NETs (GEP-NETs) and 1–2% of all pancreatic neoplasms. In the last two decades, the increased diagnosis of pNETs has generated great interest and the development of different classifications, grading and staging systems. Recently, several trials were performed in order to improve the knowledge of biomarkers and imaging and to provide an early diagnosis, but their role is still under debate. Nowadays, surgery represents the only curative approach for pNETs. Approximately 90% of pNETs are silent and non-functional; therefore, most patients are diagnosed in late stage and present metastatic (60%) or locally unresectable advanced disease (21%) with a poor prognosis. Not many therapeutic options are available for pNETs, with different treatments for G1-G2 and G3 tumors, because these diseases are still rare and trials are made up of few series of patients. At present, medical treatments is controversial. On these bases, we believe that a multidisciplinary team composed of surgeons, oncologists, endocrinologists, radiation oncologists, radiologists, pathologists and medicals nuclear is required. This paper presents a review of present state-of-the-art in the field of pNETs.